2013
DOI: 10.1186/2052-1847-5-15
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical study comparing two fixation methods in depression fractures of the lateral tibial plateau in porcine bone

Abstract: BackgroundA novel method of fixation has been described for the treatment of pure depression fractures of the lateral tibial plateau. Fracture fragments are elevated through a reamed transtibial tunnel. An interference screw is then passed into the tunnel to buttress fracture fragments from beneath. This method of fixation has perceived benefits but there have been no studies to demonstrate that the technique is biomechanically sound. The aim of our study is to compare traditional parallel, subchondral screw f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…It has to be noted that the biomechanical test set-up used for this study reduced the acting forces on the tibial plateau to the main axial loading forces, and here on the lateral part of the plateau. However, even if this set-up cannot completely simulate the physiological conditions, it compares well with former biomechanical studies using similar test set-ups 12 , 14 16 , 24 , and this study contributes important biomechanical information about the differences in stability of several treatment options. We also recognize that the use of the indentor loaded exclusively the reduced fracture fragment and therefore created a more rigorous test set-up as an artificial knee joint as load applicator would have done.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…It has to be noted that the biomechanical test set-up used for this study reduced the acting forces on the tibial plateau to the main axial loading forces, and here on the lateral part of the plateau. However, even if this set-up cannot completely simulate the physiological conditions, it compares well with former biomechanical studies using similar test set-ups 12 , 14 16 , 24 , and this study contributes important biomechanical information about the differences in stability of several treatment options. We also recognize that the use of the indentor loaded exclusively the reduced fracture fragment and therefore created a more rigorous test set-up as an artificial knee joint as load applicator would have done.…”
Section: Discussionsupporting
confidence: 53%
“…Benoit et al 15 analysed a new option of filling the metaphyseal bone defect with trabecular metal, revealing that a higher stability was achieved with this technique compared to an impacted cancellous bone graft in tibial head depression fractures. Furthermore, Blakey et al 16 simulated higher loading conditions when investigating an interference screw as an osteosynthesis alone in pure depression fractures of the tibial plateau. Under high loading conditions, low stability was found for the interference screw alone why using this osteosynthesis alone is not reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…The biomechanical test set-up is similar to former studies in literature with regard to loading level, number of cycles, separating load-to-failure and cyclic testing, and concentrating on the main axial forces on the tibial plateau [28,44,45]. In contrast to separated load-to-failure and cyclic testing, McDonald et al [46] designed a testing protocol with continuously increasing loading levels over a higher number of cycles overall.…”
Section: Discussionmentioning
confidence: 99%
“…The interference screw technique (bioabsorbable screw in the tunnel) was first described by Lubowitz et al [16] for arthroscopic reduction and fixation of depression fracture without any other fixation. However, a recent biomechanical study in porcine bone has shown that a construct with this screw only achieves a lower strength than with two subchondral screws [17]. Thus, we think that this technique should not be used alone.…”
Section: Discussionmentioning
confidence: 97%